RETRACTED: Optimizing urban eco-efficiency: Exploring the interplay of data analytics, iot integration, and cybersecurity in smart cities of the UAE - Onyusheva Irina; Dudukalov Egor; Shatila Khodor; Voronina Alexandra; Ushakov Denis (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001